Value Management Concept in Construction Projects Delivery in Kano State - Dahiru, Alhassan (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Construction projects delivery play an important role in the economic development of any nation. Nevertheless, review of project documents in Nigeria and Kano State in particular indicates that, the design of these projects is such that the whole life-value is not achieved. One of the suitable tools for the compensation of this drawback is the use of Value Management (VM) technique. This paper presents that the use of organized framework for the VM technique in the initial phase of a project generates good ideas that has the capacity to increase the project value. The objective of the study is to investigate the application of the VM in public construction projects, identify the constraint factors limiting its application, and suggest ways to expand its use in the built environment. Questionnaire survey methodology, addressed to government ministries and agencies actively involved in construction and to project management consulting firms, was utilized. A total of 94 questionnaires responses were received from 7 ministries and agencies. Another 13 responses were received from randomly selected consulting firms. The data was analyzed using SPSS 23 version. It was found that value management as a formal programme is not applied to the development of construction projects in Kano State. Lack of knowledge about the value management technique and its financial and technical benefits was found to be among the constraint factors of its application. Furthermore, lack of government demand on VM, unfamiliarity with VM technique, and unavailability of experts to perform were determined to be the top constraint factors. Therefore, it is recommended that the promotion of value management use can be achieved by creating awareness among the construction stakeholders, gaining top management support, providing training programmes, guideline, and financial incentives to procurement administrators.